Utilization of Alum Sludge from Water Treatment Plant as an Adsorbent for Hydrogen Sulfide Removal - Nguyen, Nhat Huy; Hien, Lam Pham Thanh; Khoa, Le Nguyen Dang; Thanh, Dang Van; Hieu, Nguyen Thi; Thuy, Vo Thi Thanh; Oanh, Tran Thi Phi (Creative Science, 2021)
Utilizing waste is one of the research directions that receive a lot of attention, especially in the field of the environment. In this study, the H2S adsorption capacity of modified sludge from Tan Hiep Water Treatment Plant (Ho Chi Minh City, Vietnam) was investigated. Scanning electron microscopy, energy- dispersive X-ray spectroscopy, and X-ray diffraction were used to analyze material properties. The effects of operating conditions such as H2S concentration and airflow rate were also surveyed. The analysis show the Tan Hiep Water Treatment Plant sludge contains metallic elements that are mainly aluminum. The appropriate temperature for calcining the raw sludge was 300 °C, and the Langmuir isotherm equation is suitable to describe H2S adsorption process in the concentration range of 50 – 400 ppm with R2 = 0.99. Under the optimal operating conditions (e.g., H2S concentration of 200 ppm and flowrate of 1 L min–1), the adsorption capacity of the alum sludge heated at 300 °C reached 36.65 mgH2S g–1, which is potential for practical H2S adsorption in biogas.